Tracing the epidemic history of HIV-1 CRF01_AE clusters using near-complete genome sequences - Li, Xingguang (Sci Rep, 2017)
Human immunodeficiency virus (HIV) has a number of circulating recombinant forms that are the product of recombination between different HIV subtypes. The first circulating recombinant form of HIV-1 to be identified was CRF01_AE, which originated in Central Africa and is now most prevalent in Southeast and East Asia. In this study, we investigated the timescale, evolutionary history, and population genetics of the HIV-1 CRF01_AE strains primarily responsible for the epidemic in Asia. A further aim of our study was to define and standardize the nomenclature and provide well-characterized reference sequences for the phylogenetic transmission clusters of CRF01_AE. We analysed a data set of 334 near-complete genome sequences from various risk groups, sampled between 1990 and 2011 from nine countries. Phylogenetic analyses of these sequences were performed using maximum likelihood and Bayesian methods. Our study confirms that the diversity of HIV-1 CRF01_AE originated in Central Africa in the mid-1970s, was introduced into Thailand between 1979 and 1982, and began expanding there shortly afterwards (1982–1984). Subsequently, multiple clusters significantly contributed to China’s HIV epidemic. A Bayesian skyline plot revealed the rapid expansion of CRF01_AE in China around 1999–2000. We identified at least eight different clusters of HIV-1 CRF01_AE formed by rapid expansion into different risk groups and geographic regions in China since the late 1980s.